2014
DOI: 10.1111/ijpp.12114
|View full text |Cite
|
Sign up to set email alerts
|

Privacy and confidentiality: perspectives of mental health consumers and carers in pharmacy settings

Abstract: This study explored mental health stakeholders' experiences and expectations regarding privacy and confidentiality in the Australian community pharmacy context. A need for better pharmacy staff training about the importance of privacy and confidentiality and strategies to enhance compliance with national pharmacy practice requirements was identified. Findings provided insight into privacy and confidentiality needs and will assist in the development of pharmacy staff training material to better support consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…Of interest was that four of the pharmacies did not have private consultation areas as they did not provide in‐pharmacy medication review services. The possible reticence of a consumer to be singled out for consultation in a counselling booth was also raised, similar to mental health consumer research …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Of interest was that four of the pharmacies did not have private consultation areas as they did not provide in‐pharmacy medication review services. The possible reticence of a consumer to be singled out for consultation in a counselling booth was also raised, similar to mental health consumer research …”
Section: Discussionsupporting
confidence: 87%
“…A recent Australian study involving 74 mental health consumers and carers found consumers are likely to form trusting relationships with community pharmacy staff if they perceive pharmacies as safe health spaces . The research identified a need for pharmacy staff to be more discreet when calling out patient names, having private conversations in the pharmacy and exposing medication packs being purchased or issued . Participants of a 2010 United Kingdom (UK) community pharmacy‐based cardiovascular screening study similarly identified concerns about confidentiality and lack of privacy as barriers to participating in screening services .…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that there is a need for some pharmacies to improve privacy and confidentiality aspects, which has also been identified as barriers in other community pharmacy alcohol screening studies [54, 56]. An Australian study that focused on privacy and confidentiality needs of mental health consumers and carers highlighted a need for increased staff training about the importance of privacy and confidentiality, workflow models to facilitate private discussions and processes and procedures to ensure confidentiality of documentation [57]. Community pharmacies providing alcohol SBI services will similarly need to ensure that these aspects are well managed.…”
Section: Discussionmentioning
confidence: 99%
“…We developed a web‐based mental health promotion intervention using the intervention mapping framework . The content, learning techniques and delivery mode for the intervention were informed by a needs assessment undertaken with Australian pharmacy staff and mental health consumers and carers who use community pharmacies . A review of the literature was also undertaken to inform the study and development of questionnaires …”
Section: Methodsmentioning
confidence: 99%
“…Personal consumer narratives, which we incorporated into the intervention materials, are a form of experiential learning technique known to achieve greater impact in reducing stigma than traditional educational approaches such as lectures . Additionally, the intervention incorporated other experiential learning techniques, such as real‐life scenarios and role‐plays, raising awareness of privacy and confidentiality issues, and the impact this can have on stigma (both self‐stigma and social stigma) when not respected, to provide participants with multiple and varied opportunities to interact with the information and improve understanding and confidence . This multifaceted and innovative intervention program was delivered in a flexible web‐based mode with a series of discrete modules proven to enhance accessibility and uptake …”
Section: Methodsmentioning
confidence: 99%